Culturally Motivated Crimes: the Cultural Test in the Italian Jurisprudence. A Comparative Study (Stato, Chiese e pluralismo confessionale, 2020)
SUMMARY: 1. Key terms and definitions - 2. Two ways to look at culturally motivated crimes: the case of the kirpan in the Italian and in the Canadian jurisprudence - 3. Moving forward: the Italian Court of Cassation n. 29613/2018 - 3.1. Cultural tests: a comparative insight - 3.2. The cultural test in the Italian judgment of 2018 - 4. Final remarks.ABSTRACT: The aim of this article is to analyze culturally motivated crimes with a comparative focus and a case law approach. First of all, a set of definitions is given to have a common and shared understanding of the topic at stake. What is culture and what do we mean by culturally motivated crimes? Secondly, a comparative case-law study helps to focus the possible different solutions given to the cultural factor in criminal law. In fact, some legal systems -such as the Canadian one - appear to be more willing than others to make concrete accommodations of cultural differences. Lastly, the latest Italian Court of Cassation suggests a possible direction to be taken to better treat culturally motivated crimes in today’s multicultural society. What does it mean for criminal law to be culturally sensitive? How can courts take into consideration cultural factors through a proper legal method? These are the main questions on which criminal doctrine has focused its attention trying to reshape a criminal model which can be responsive to those different cultural values, needs and interests.